Portuguese language workshop: memorial of readings in higher education - Pereira, Daniervelin Renata (Universidade Estadual de Campinas, 2019)
This work presents a lived experience in an introductory class of the course of Letters in the face-to-face course “Oficina de Língua Portuguesa”, offered by the Faculty of Letters of the Federal University of Minas Gerais in 2017. This experience occurred in the context of language teaching and learning Portuguese in higher education around the production of memorials on reading learning. For the report, we present some concepts that support our practices, such as: reading models, reading the “palavramundo”, Pedagogy of multiliteracies, memory and Open Educational Resources. We then proceeded to the descriptive and analytical account of the stages that involved discussions in the classroom and organization of a group of interested parties in the edition of an e-book that gathered the memorials of the students. The independent production of the texts produced by the students served to consolidate the pedagogical practices in the classroom and beyond, within the objectives inscribed in the discipline, to value the memories of each student and also as a way to inspire readers and get them to reflect on the process of reading. We have also mentioned other open educational resources built for the didactic activities, which have been published and are available on-line. The results of this experience point to the importance of a didactic work with specific questions of reading and writing that involves the engagement of undergraduates in collaborative and dynamic activities, relating intelligible and sensitive.